Bias perilaku dan persepsi risiko dalam pembuatan keputusan investasi: Peran moderasi literasi keuangan - Andronius Purnomo; Werner Ria Murhadi; Liliana Inggrit Wijaya (Jurnal Manajemen Maranatha, 2025)
Behavioral finance highlights that investors frequently encounter errors in making investment decisions due to cognitive and emotional biases, leading to less-than-optimal investment outcomes. These biases are inherently challenging to overcome and significantly shape how decisions are made. The human brain often relies on shortcuts and emotional interpretations when processing information, resulting in flawed judgments. This research seeks to analyze and assess the impact of the disposition effect, herding behavior, overconfidence, and risk perception on investment decisions, while also investigating the moderating influence of financial literacy. Utilizing a non-probability sampling technique, the study involves 165 respondents and applies structural equation modeling (SEM) analyzed through SPSS AMOS. The results reveal that disposition effect, herding behavior, overconfidence, and risk perception have a substantial impact on investment decisions, whereas financial literacy does not notably moderate their effects on the decision-making process.